The Effect of Slow Deep Breathing on Dyspnea Reduction in Heart Failure Patients: Literature Review - Heni Nurhaeni (Badan Riset dan Inovasi Nasional, 2022)
The heart is one of the most important organs/vital organs for the human body which has a role in circulating the supply of oxygen and nutrients to all body tissues and organs needed in metabolism. The World Health Organization (2021) reports that an estimated 17.9 million people died from cardiovascular disease in 2019, representing 32% of all global deaths. The prevalence in Indonesia also has a high number of people with heart disease. Purpose : Knowing whether there is an effect of deep breathing exercise on the level of dyspnea in heart failure. Methods : The protocol and evaluation of the literature review will use the PRISMA checklist to determine the selection of studies that have been found and adapted to the objectives of the literature review (Nursalam, 2020). The literature search was carried out on August 1 – 26, 2022. Results : The data used in this study is secondary data obtained not from direct observation, but obtained from the results of research that has been carried out by previous researchers. The literature search in this literature review uses five databases with high and medium-quality criteria. The effect of deep breathing exercises in reducing dyspnea in heart failure patients. Conclusion : The results of the literature review prove that deep breathing exercises can affect the reduction of dyspnea in heart failure patients.